2020
DOI: 10.1002/acr.23887
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Differences in the Prevalence and Time to Onset of Manifestations of Systemic Lupus Erythematosus: The California Lupus Surveillance Project

Abstract: Objective. The California Lupus Surveillance Project (CLSP) is a population-based registry of individuals with systemic lupus erythematosus (SLE) residing in San Francisco County, California from 2007 to 2009, with a special focus on Asian/Pacific Islander and Hispanic patients. We used retrospective CLSP data to analyze racial and ethnic differences in lupus manifestations and in the timing and risk of developing severe manifestations.Methods. A total of 724 patients with SLE were retrospectively identified. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 25 publications
2
74
0
5
Order By: Relevance
“… 13 In the USA, African-American women are at 3 times the risk of SLE compared with white women and also tend to experience more severe SLE, potentially causing greater ovarian toxicity. 19–21 Thus, the relationship between SLE and ovarian reserve as measured by AMH may differ among African-American women.…”
Section: Introductionmentioning
confidence: 99%
“… 13 In the USA, African-American women are at 3 times the risk of SLE compared with white women and also tend to experience more severe SLE, potentially causing greater ovarian toxicity. 19–21 Thus, the relationship between SLE and ovarian reserve as measured by AMH may differ among African-American women.…”
Section: Introductionmentioning
confidence: 99%
“…9 Indeed, racial and ethnic differences have recently been analyzed by the California Lupus Surveillance Project, and it was found that Hispanic patients showed an increased risk of developing severe manifestations such as LN, thrombocytopenia, and APS earlier than Caucasian patients following an SLE diagnosis. 23 The main complication of SLE at admission was LN, with a considerable percentage of patients requiring renal replacement therapy. A study by Diaz-Coronado et al.…”
Section: Discussionmentioning
confidence: 99%
“…Racial and ethnic differences were recently analyzed in lupus manifestations and in the timing and risk of developing severe manifestations in the California Lupus Surveillance Project (CLSP) [9 ▪ ]. This was the first epidemiologic study of lupus comparing manifestations among the four-major racial/ethnic groups in the United States: blacks, whites, Asian/Pacific Islanders (APIs), and Hispanics.…”
Section: Advancing Lupus Health Disparities Research In the United Stmentioning
confidence: 99%
“…A consistent finding of epidemiological studies is the higher incidence of lupus nephritis and end-stage renal disease in Blacks and Hispanics with SLE [1,9 ▪ ,28,37,38]. A US group analyzed records in the United Network for Organ Sharing program and Standard Transplant Analysis and Research files to compare kidney allograft survival in African-American and Hispanic individuals who had SLE and received kidney transplants between 1987 and 2006 [39].…”
Section: Other Research Targeting High-risk Populations With Systemicmentioning
confidence: 99%